Ten Common Statistical Errors from All Phases of Research, and Their Fixes. - Borg, David N.; Lohse, Keith R.; Sainani, Kristin L. (PM & R: Journal of Injury, Function & Rehabilitation, 2020)
Statistical errors are surprisingly common and threaten the credibility of biomedical research.[[1], [3]] This issue has received increasing attention in recent years, including in the popular media,[[4], [6]] prompting calls for statistical reform. We present examples of 10 common mistakes that occur during four phases of research: study design; data wrangling and cleaning; data analysis; and reporting. B Solution: b The authors should have designed the study as a noninferiority trial, which aims to show that one intervention is not "unacceptably worse" than another.[14] In a noninferiority study, researchers specify I a priori i a noninferiority margin - a difference that would be considered too small to care about (eg, an increase in adiponectin of 0.5 mg/L). Conclusions Statistical errors can occur during all phases of a study, from study design to reporting.